Estimating a Fiscal Reaction Function The Case of Debt Sustainability in Brazil - de Mello, Luiz (OECD Economics Department Working Papers, 2005)
This paper reviews recent trends in fiscal performance in Brazil, estimates fiscal reaction functions for the consolidated public sector and different levels of government, and tests for the sustainability of the public debt dynamics. The empirical analysis, based on monthly data for the period 1995-2004, suggests that all levels of government react strongly to changes in indebtedness by adjusting their primary budget surplus targets. In addition, the central government appears to follow a spend-and-tax policy: changes in revenue are affected strongly by expenditure, with about two-thirds of changes in primary spending being offset through higher revenue over the long term. Institutions are also found to matter for fiscal sustainability. The responsiveness of sub-national fiscal stance to indebtedness, as well as that of central government revenue to changes in primary spending, appears to have strengthened after 1998, when ceilings on indebtedness were introduced